Foundations of stress waves - Wang, Li-li (Elsevier, 2007)
The primary objective of this work is to give the reader an understanding of stress wave behaviour while taking into account the dynamic constitutive equations of elastic-plastic solids. The author has combined a 'materials characteristics' approach with a 'singularity surface' approach in this work, which readers will find to be a novel and unique route to solving their problems. * Helps engineers understand the effects and behavior of stress waves in various materials * Aids in the process of engineering design, testing, and evaluation.